Effects of coffee consumption on health - Berlis Gómez Leyva; María Teresa Díaz Armas; Regla Cristina Valdés Cabodevilla; Manuel Alejandro Miguel Cruz (Medisur, 2021)
Coffee is one of the most important commercial products, and 70-80% of the world population consumes it. A bibliographic review was carried out in order to describe the effects of coffee consumption on health. For this, accessible scientific articles were located and consulted in the Pubmed and SciELO databases. Original articles, bibliographic reviews, systematic reviews, meta-analyzes and clinical trials published in the last five years were mainly used. Coffee consumption has been associated with a lower risk of several chronic diseases. Current evidence does not justify recommending coffee intake for disease prevention, but suggests that in adults without specific health problems, and in non-pregnant women, its moderate consumption can be part of a healthy lifestyle.